Determining the Effect of Drying Time on Phosphorus Solubilization from Three Agricultural Soils under Climate Change Scenarios. Issue 5 (1st September 2017) - Forber, K. J.; Ockenden, M. C.; Wearing, C.; Hollaway, M. J.; Falloon, P. D.; Kahana, R.; Villamizar, M. L.; Zhou, J. G.; Withers, P. J. A.; Beven, K. J.; Collins, A. L.; Evans, R.; et al.
Abstract : Climate projections for the future indicate that the United Kingdom will experience hotter, drier summers and warmer, wetter winters, bringing longer dry periods followed by rewetting. This will result in changes in phosphorus (P) mobilization patterns that will influence the transfer of P from land to water. We tested the hypothesis that changes in the future patterns of drying–rewetting will affect the amount of soluble reactive phosphorus (SRP) solubilized from soil. Estimations of dry period characteristics (duration and temperature) under current and predicted climate were determined using data from the UK Climate Projections (UKCP09) Weather Generator tool. Three soils (sieved <2 mm), collected from two regions of the United Kingdom with different soils and farm systems, were dried at 25°C for periods of 0, 2, 4, 5, 6, 8, 10, 15, 20, 25, 30, 60, and 90 d, then subsequently rewetted (50 mL over 2 h). The solubilized leachate was collected and analyzed for SRP. In the 2050s, warm period temperature extremes >25°C are predicted in some places and dry periods of 30 to 90 d extremes are predicted. Combining the frequency of projected dry periods with the SRP concentration in leachate suggests that this may result overall in increased mobilization of P; however, critical breakpoints of 6.9 to 14.5 d dry occur wherein up to 28% more SRP can be solubilized following a rapid rewetting event. The precise cause of this increase could not be identified and warrants further investigation as the process is not currently included in P transfer models. Core Ideas: UK Climate Projections predict long dry hot periods followed by intense rainfall. Frequency of longer dry periods increase under climate change. Critical breakpoints of 7–15 dry days have been identified that solubilize more P from soil. Increased dry period frequency will result in an overall increase in SRP concentration solubilized.